Multimodal Wheelchair Control for the Paralyzed People - Maskeliunas, R.; Simutis, R. (Elektronika ir Elektrotechnika, 2011)
Most serious accidents and injuries often end with various motoric disabilities usually resulting in a limited control of the muscles of various body parts and in some worst case scenario even the whole body. The associated governmental support programs of today are targeted at providing the technological means enabling the handicapped persons to have as independent life as possible. In the presented research authors concentrate on the development of a mobility device for the paralyzed people, trying to develop an effective multimodal HCI algorithm by combining the traditional input with speech and video recognition technologies into one associative "package". Paper reviews some of the associated research on the topic, a proposed algorithm for the multimodal wheelchair control and a scheme of implementation. Ill. 2, bibl. 17 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.111.5.362